2007
DOI: 10.2174/092986707780831131
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Inflammatory Pathways - Implications for Vascular Disease, Vascular Risk and Therapeutic Intervention

Abstract: Cardiovascular disease remains the most common cause of death worldwide, yet there is a wide variation in disease prevalence between different ethnic groups. One's individual risk is not entirely explained by 'traditional' risk factors and this, along with the observation that endogenous and lifestyle risk factors appear to cluster in the same individuals has led to the idea that there may be a common mechanism underlying this disease. It has been postulated that inflammatory pathways may be important. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 165 publications
(261 reference statements)
2
27
0
Order By: Relevance
“…11 This finding was reflected in the recent amendment to the FDA license for rosuvastatin. Although median CRP concentrations have been reported previously to vary among populations of differing ancestry, 23 individual studies have been too small in size to estimate these differences precisely. If substantial, as we now confirm, this could lead to ethnicity being an impor- …”
Section: Discussionmentioning
confidence: 94%
“…11 This finding was reflected in the recent amendment to the FDA license for rosuvastatin. Although median CRP concentrations have been reported previously to vary among populations of differing ancestry, 23 individual studies have been too small in size to estimate these differences precisely. If substantial, as we now confirm, this could lead to ethnicity being an impor- …”
Section: Discussionmentioning
confidence: 94%
“…26 In conclusion, the TBL1Y A USP9Y A haplotype of the Y chromosome, present only in black people of African origin, attributes a favorable lipoprotein pattern, likely to contribute to their reduced susceptibility to develop atherosclerosis and coronary heart disease in Africa, the Caribbean, and the UK. [27][28] …”
Section: Russo Et Al Y Chromosome Variants and Cardiovascular Riskdismentioning
confidence: 99%
“…3,4 Research has demonstrated differences in the level of circulating immune/inflammatory markers as well as genotypic differences which may help to explain disease predisposition in specific racial groups. 3,4 In contrast, there is limited information relating to immune/inflammatory responses to exercise between racial groups. Such information is particularly relevant -strenuous exercise has been shown to alter immune/inflammatory responses predisposing athletes to infection and possibly injury, 5 which would ultimately impact on training and performance.…”
mentioning
confidence: 99%